On Cooperative Behavior in Distributed Teams: The Influence of Organizational Design, Media Richness, Social Interaction, and Interaction Adaptation - Håkonsson, Dorthe D.; Obel, Børge; Eskildsen, Jacob K.; Burton, Richard M. (Frontiers in Psychology, 2016)
Self-interest vs. cooperation is a fundamental dilemma in animal behavior as well as in human and organizational behavior. In organizations, how to get people to cooperate despite or in conjunction with their self-interest is fundamental to the achievement of a common goal. While both organizational designs and social interactions have been found to further cooperation in organizations, some of the literatures have received contradictory support, just as very little research, if any, has examined their joint effects in distributed organizations, where communication is usually achieved via different communication media. This paper reviews the extant literature, and offers a set of hypothesis to integrate current theories and explanations. Further, it discusses how future research should examine the joint effects of media, incentives, and social interactions.